Association between Atherogenic index of plasma and gallstones in the United States adults: A cross-sectional analysis of NHANES 2017–2020 - Shuang Yang; Jianhui Song; Zhengbo Yang; Nanbo Li; Ju Wu; Shuangshuang Hou (Preventive Medicine Reports)
Background: Although substantial evidence suggests an association between dyslipidemia as an isolated factor and gallstones, research on the Atherogenic Index of Plasma (AIP) and gallstones remains limited. Methods: A total of 3557 eligible adults from the United States were selected for cross-sectional analysis using the 2017–2020 National Health and Nutrition Examination Survey database. Logistic regression was employed to evaluate the association between AIP gallstones. Restricted cubic spline (RCS) analysis and threshold effect analysis were conducted to explore potential non-linear relationship. Results: The study found a positive association between higher AIP levels and higher odds of gallstones. In the fully adjusted logistic regression model, each 1-unit increase in AIP was associated with 59 % higher odds of gallstones (OR = 1.59, 95 % CI: 1.06, 2.38). Compared to the lowest quartile of AIP, the highest quartile showed 82 % higher odds of gallstones (OR = 1.82, 95 % CI: 1.23, 2.69). RCS analysis revealed a non-linear relationship between AIP and gallstones, with threshold effect analysis identifying a turning point at −0.13, where AIP had a positive correlation with gallstones before this threshold. Conclusion: Higher AIP is positively correlated with higher odds of gallstones, showing a non-linear relationship. As AIP increases, the odds of gallstones also rise, but this relationship is no longer observed beyond a certain threshold. It is recommended to maintain appropriate AIP levels to reduce the incidence of gallstones.